Atomic-scale engineering of indium oxide promotion by palladium for methanol production via CO2 hydrogenation - Matthias S. Frei (Nature Portfolio, 2019)
Generating and quantifying the effect of the promoter speciation in heterogeneous catalysts is very challenging. Here, the authors show that the precise palladium atoms architecture reached by controlled co-precipitation overcomes selectivity and stability limitations associated with palladium nanoparticles for CO2-based methanol synthesis.